Sport in America from colonial leisure to celebrity figures and globalization Volume II - Wiggins, David Kenneth 1951- (Champaign, IL Human Kinetics, 2010)
Sport in America: From Colonial Leisure to Celebrity Figures and Globalization, Volume II, presents 18 thought-provoking essays focusing on the changes and patterns in American sport during six distinct eras over the past 400 years. The selections are entirely different from those in the first volume, discussing diverse topics such as views of sport in the Puritan society of colonial New England, gender roles and the croquet craze of the 1800s, and the Super Bowl's place in contemporary sport. Each of the six parts includes an introduction to the essays, allowing readers to relate them to the cultural changes and influences of the period. Readers will find essays on well-known topics written by established scholars as well as new approaches and views from recent studies. Suitable for use as a stand-alone or supplemental text in undergraduate and graduate sport history courses, Sport in America provides students with opportunities to examine selected sport topics in more depth, realize a greater understanding of sport throughout history, and consider the interrelationships of sport and other societal institutions. Essays are arranged chronologically from the early American period to the present day to provide the proper historical context and offer perspective on changes that have occurred in sport over time. Also, a list of suggested readings provided in each part offers readers the opportunity to expand their thinking on the nature of sport throughout American history. Essays on how Pinehurst Golf Course was created, the interconnection between sport and the World War I military experience, and discussion of sport icons such as Joe Louis, Walter Camp, Jackie Robinson, and Cal Ripken Jr. allow readers to explore sport as a reflection of the changing values and norms of society. Sport in America: From Colonial Leisure to Celebrity Figures and Globalization, Volume II, provides students and scholars with perspectives regarding the role of sport at particular moments in American history and gives them an appreciation for the complex intersections of sport with society and culture.
Part I. The Pattern of Sport in Early America, 1607-1776 -- Chapter 1. Sober Mirth and Pleasant Poisons: Puritan Ambivalence Toward Leisure and Recreation in Colonial New England / Bruce C. Daniels -- Chapter 2. Horses and Gentlemen: The Cultural Significance of Gambling Among the Gentry of Virginia / T. H. Breen -- Part II. Transformation of Sport in a Rapidly Changing Society, 1776-1870 -- Chapter 3. Pedestrianism, Billiards, Boxing, and Animal Sports / Melvin L. Adelman -- Chapter 4. Cheating, Gender Roles, and the Nineteenth-Century Croquet Craze / Jon Sterngass -- Chapter 5. The National Game / Warren Goldstein -- Part III. Sport in the Era of Industrialization and Reform, 1870-1915 -- Chapter 6. Sporting Life as Consumption, Fashion, and Display--The Pastimes of the Rich / Donald J. Mrozek -- Chapter 7. Creating America's Winter Golfing Mecca at Pinehurst, North Carolina: National Marketing and Local Control / Larry R. Youngs -- Chapter 8. The Father of American Football / Michael Oriard -- Part IV. Sport, The Great Depression, and Two World Wars, 1915-1950 -- Chapter 9. The World War I American Military Sporting Experience / S.W. Pope -- Chapter 10. In Sports the Best Man Wins: How Joe Louis Whupped Jim Crow / Theresa E. Runstedtler -- Chapter 11. Padres on MountOlympus: Los Angeles and the Production of the 1932 Olympic Mega-Event / Sean Dinces -- Chapter 12. Going to Bat for Jackie Robinson: The Jewish Role in Breaking Baseball's Color Line / Stephen H. Norwood and Harold Brackman -- Part V. Sport in the Age of Television, Discord, and Personal Fulfillment, 1950-1985 -- Chapter 13. Toil and Trouble: A Parable of Hard Work and Fun / David W. Zang -- Chapter 14. Victory for Allah: Muhammad Ali, the Nation of Islam, and American Society / David K. Wiggins -- Chapter 15. The Fight for Title IX / Pamela Grundy and Susan Shackelford -- Part VI. Sport During the Period of Celebrity and Globalization, 1985-Present -- Chapter 16. Yearning for Yesteryear: Cal Ripken, Jr., The Streak, And the Politics of Nostalgia / Daniel A. Nathan and Mary G. McDonald -- Chapter 17. Manhood, Memory, and White Men's Sports in the American South / Ted Ownby -- Chapter 18. The Whole World Isn't Watching (But We Thought They Were): The Super Bowl and U.S. Solipsism / Christopher R. Martin and Jimmie L. Reeves.
Includes bibliographical references
Keywords: Sports -- United States -- History; Sports -- Social aspects -- United States -- History